Development of a Water‐Dispersible SBA‐15‐Benzothiazole‐Derived Fluorescence Nanosensor by Physisorption and Its Use in Organic‐Solvent‐Free Detection of Perborate and Hydrazine. Issue 38 (10th October 2018) - Gawas, Ram U.; Anand, Shivesh; Ghosh, Barun K.; Shivbhagwan, Princee; Choudhary, Kushav; Ghosh, Narendra Nath; Banerjee, Mainak; Chatterjee, Amrita
Abstract: We have synthesized a water dispersible SBA‐15 based sensing material (nanosensor1 ) for the detection of perborate ions and hydrazine in water. The nanosensor was prepared by simple physisorption of chemosensing unit 2‐(benzo[ d ]thiazol‐2‐yl)phenyl acetate (2 ) onto PEG‐stabilized SBA‐15. The probe molecule undergoes spontaneous cleavage of acetate group in the presence of both perborate ions and hydrazine to produce corresponding phenol (3 ), which results in greenish blue fluorescence by excited state intra‐molecular proton transfer (ESIPT) mechanism. The limit of detection (LOD) for both analytes was observed in ppb level; 49.9 ppb for perborate ions and 8.0 ppb for hydrazine. Simple synthesis, effortless modification, high water dispersibility make this nanosensor very efficient for perborate ions and hydrazine. Finally, this is a demonstration of the physisorption strategy in building useful sensing materials which can be applied to any analyte based on the choice of a suitable chemosenors. Abstract : A water dispersible SBA‐15 based sensing material (nanosensor1 ) was developed by simple physisorption of chemosensing unit 2‐(benzo[ d ]thiazol‐2‐yl)phenyl acetate (2 ) onto PEG‐stabilized SBA‐15 and used for the detection of perborate ions and hydrazine in water by excited state intramolecular proton transfer (ESIPT) mechanism. The limit of detection (LOD) was observed as 49.9 ppb for perborate ions and 8.0 ppb for hydrazine. Simple synthesis, effortless modification, high water dispersibility are some key features of this nanosensor.